Myth In The Story Of Serat Panji Narawangsa Horse And Raden Klana In Wayang Beber Pacitan - Fitri Pramadhanti, Dhelinta; Gusty, Nency; Oktaviani Br Ginting, Dasa; Metyawati Nur Afifah, Dyah (International Proceedings of Nusantara Raya, 2022)
This research is a structural study of Levi-Strauss which analyzes the myths contained in the Panji story in the Serat Kuda Narawangsa version and Raden Klana in the Pacitan Wayang Beber version of the story. The results of this study are that there are myths contained in the Serat Kuda Narawangsa, namely a female giant creature with the power of disguise as Dewi Sekartaji and the magic of Raden Gunungsari who shoots a female giant who then runs and flies with his strength. Then, in the Pacitan Wayang Beber story there is a myth that is contained in the character Raden Klana Sawendana can change form into Raden Gandarepa with his supernatural powers, besides that there is a myth that is contained, namely Ki Tawang Alun using the Pasopati Keris to kill Raden Klana Sawendana. It can be concluded that the story of the banner in the version of Serat Kuda Narawangsa and Wayang Beber Pacitan has a myth that can be analyzed using a structural study from Levi-Strauss which does not have to be contrasted with history or reality because it is considered a fairy tale even though in the storyline there is a reflection of the life of the people who own the fairy tale.